Evaluación Presupuestaria al Gobierno Autónomo Descentralizado Parroquial Rural de Timbara, Cantón Zamora, Periodo 2015” - Romero Cobos, Damaris Lizbeth (2015)
The thesis, entitled "BUDGET EVALUATION TO THE DECENTRALIZED AUTONOMOUS GOVERNMENT OF TIMBARA RURAL PARISH, CANTÓN ZAMORA, PERIOD 2015", which was carried out through the evaluation of the budget in relation to the distribution of the income and expenses elicited by the same requesting the information Pertinent and necessary for the development of this thesis, such as: the Annual Operative Plan, Initial Budget, Budget Execution Status, Income and Expenditure Budget Documents; In addition the compilation of the bibliographic material based on the budgetary regulations, laws, codes and regulations issued by the Ministry of Finance. In order to comply with the first objective in the budget evaluation phase, the plans, programs, projects and activities established in the Institution's Annual Operational Plan were evaluated, by means of which it was determined that the entity had programmed 39 activities of Which were complied with 25 having as a percentage a 64.10% of compliance with what is programmed in the Annual Operational Plan for the year 2015. After the evaluation of the Operational Plan, the respective budget indicators were applied, which was applied to measure the efficiency and 5 effectiveness of the management of the activities, determining that according to the results, the entity has not implemented all the scheduled activities. Which are planned, in the end are not fulfilled by the lack of economic resources, so it was evident that the Directors are not determined to efficiently manage and execute the resources that correspond to the Parish Board. Finally, in the analysis of the Annual Operational Plan and the application of indicators, it was possible to have the information necessary to conclude with the presentation of the Budget Evaluation Report of the Timbara Rural Parish Government, which shows the results of the planned and executed activities, Conclusions and recommendations for consideration by the Directors. Finally, the conclusions and recommendations were formulated with their respective bibliography.